Propuesta de diseño e implementación de un sistema de gestión integrado para una empresa del sector comercial. - Falconí Anzules, Vicente (2010)
The present work contains the development of an offer of design and implementation of a System of Management Integrated for a company of the commercial sector, with the scope in the areas of administration and commercialization. The current project allows adopting the requirements and guidelines of the ISO procedure 9000, ISO 14000 and OHSAS 18000 to the particular characteristics of the organization. The alternatives and solutions have been adapted to the draft of the business. Based on the focusing to processes and the philosophy of the endless improvement it permits integrate in a same system, the step of the quality, environmental step and step of the security and health in the work. The Implementation of the procedure permits characterize it organization object of study, the realization of a diagnosis in which it is verified the main deficiencies and the confection of a plain of action to eradicate them or minimize them. The procedure facilitates moreover the identification of the processes, the chips of the processes identified, the procedures for each process and indicators for your measurement and control